Strategic uncertainty and probabilistic sophistication - Masaki Aoyagi; Takehito Masuda; Naoko Nishimura (Osaka University, Institute of Social and Economic Research (ISER), 2021)
This paper uses laboratory experiments to study subjects' assessment of uncertainty resulting from strategic and non-strategic decisions of other players. Nonstrategic events are defined by the colors of balls drawn from urns, whereas strategic events are defined by the action choice in Stag Hunt (SH) and Prisoners' Dilemma (PD) games. We elicit subjects' matching probabilities and examine if they satisfy the law of probability including monotonicity and additivity. Violations from the law are observed for both uncertainty sources, but are more substantial for strategic uncertainty. In particular, we observe a coordination fallacy, a violation of monotonicity whereby the probability weight placed on a symmetric coordination profile of the games exceeds that placed on the corresponding action choice. The violation is found to be severer for an efficient coordination profile.
Keywords: C91; D01; D81; D91; 330; matching probability; ambiguity; uncertainty; coordination; conjunction